(On) Searle on Conversation : Compiled and introduced by Herman Parret and Jef Verschueren. - Searle, John R. (John Benjamins Pub. Co., 1992)
At an international conference held in 1981 at the Universidada Estudual of Campinas (Brazil), a controversial lecture was given by John Searle which presented two conceptual theses: that conversation does not have an intrinsic structure about which a relevant theory can be formulated, and that conversations are not subject to (constitutive) rules. This lecture was first published in 1986 under the title "Notes on Conversation", and was revised several times afterwards. The present volume offers the most recent version. Because of the importance of the article for conversation analysis, and fo.